2020 IEEE Frontiers in Education Conference (FIE) 2020
DOI: 10.1109/fie44824.2020.9274237
|View full text |Cite
|
Sign up to set email alerts
|

On the Differences in Time That Students Take to Write Solutions to Programming Problems

Abstract: Full research paper-In this work, we study productivity differences in an introductory programming course. Focusing on a set of students who completed all programming assignments in the course, we quantify differences in productivity, measured through the time spent on completing the assignments. We focus both on the overall time needed to complete all programming assignments in the course, as well as on time spent on individual programming assignments. In addition, the effect of previous programming experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In education, stereotypes and personal understanding can affect a student's attitude to whether programming is something they could engage in; for example, the idea of a "geek gene" (that some people are inherently born as programmers) is a commonly held view despite being widely refuted [2,49,63,101,102] (although there can be significant differences between outcomes for students in programming courses, and in the time taken to write programs). Even the misconceptions that parents have about programming can have a flow on effect onto how well their children do in computer science [81].…”
Section: Psychological Social and Ethical Concernsmentioning
confidence: 99%
“…In education, stereotypes and personal understanding can affect a student's attitude to whether programming is something they could engage in; for example, the idea of a "geek gene" (that some people are inherently born as programmers) is a commonly held view despite being widely refuted [2,49,63,101,102] (although there can be significant differences between outcomes for students in programming courses, and in the time taken to write programs). Even the misconceptions that parents have about programming can have a flow on effect onto how well their children do in computer science [81].…”
Section: Psychological Social and Ethical Concernsmentioning
confidence: 99%
“…Interestingly, we found that when examining students grouped by how many days before the deadline they started to work on assignments and how many days they worked (see Figure 4), in some cases for students who start on the same day, those who end up working on fewer days tend to perform better in the course on average. One possible explanation for this is that high performing students require fewer days to complete assignments -prior work has shown that there are substantial differences in the time it takes students to solve programming problems [11]. However, this also means that at least some students who exhibit the "ideal" work habits of both starting early and working on multiple days will nevertheless perform poorly in the exam.…”
Section: Early Start = Better Grade: Not That Simplementioning
confidence: 99%